2009
DOI: 10.1080/17538150902773272
|View full text |Cite
|
Sign up to set email alerts
|

Health-related Internet use by patients with somatic diseases: Frequency of use and characteristics of users

Abstract: The aim of this study was to explore the percentage of Dutch patients using the Internet to search for information about their illness. In addition, we studied patients' usage of health-related Internet applications, such as online patient support groups. The final objective of this study was to explore which demographic, health and psychological characteristics are related to patients' health-related Internet use. In order to answer these research questions we sent a written questionnaire to a representative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
69
4
8

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 41 publications
(71 reference statements)
10
69
4
8
Order By: Relevance
“…But it is about 10% greater than that reported in a sample of Dutch patients (that included breast cancer patients) conducted a year earlier [18]. This may be because of the unique characteristics of the sample.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…But it is about 10% greater than that reported in a sample of Dutch patients (that included breast cancer patients) conducted a year earlier [18]. This may be because of the unique characteristics of the sample.…”
Section: Discussioncontrasting
confidence: 43%
“…Specifically, 37% read someone else's experience of a health issue on an online group, website or blog compared to 31% of those reporting no chronic conditions. A hospital-based survey of 679 Dutch patients with breast cancer, rheumatoid arthritis or fibromyalgia published in 2009 found that 15% of the patients surveyed had used an online community [18].…”
mentioning
confidence: 99%
“…The relatively low levels of health-related online activity among patients with chronic diseases may be a potential obstacle for their acceptance of more advanced e-health applications. The prevalence of information searching among health-related activities in the Internet was seen in the survey reported by van Uden-Kraan et al 44 This also applies to the infrequent use of more advanced forms of interaction (e.g., joining online patient support groups or posing questions about the patient's medical condition to experts). The responses to items listed here were ranked on a 5-point Likert scale.…”
Section: Health-related Activities Performed Onlinementioning
confidence: 78%
“…44 The effect of higher education has also been reported for specific patient populations by many authors. 35,45,47,[49][50][51][52] This effect was also seen in surveys carried out in the general population.…”
Section: Factors Affecting the Acceptance Of E-health Applicationsmentioning
confidence: 81%
“…2,38 While physicians are the preferred source of information, 9,13,22,35,40 in reality, caregivers turn to the Internet for answers first, especially for rare and chronic conditions. 9,13 While Internet use is becoming nearly universal, the Pew Internet and American Life Project, 8,11,18,36 Health Information National Trends Survey (HINTS), 22,26,28 and disease-specific studies 2,6,20,34,37,39 have found that socioeconomic disparities create a digital divide between patient populations. Interestingly, use of social media is reported to permeate all race, economic, and educational strata.…”
mentioning
confidence: 99%